Investigation into the Abnormal Phenomenon of Rail Corrugation Superposition in Small-Radius Curve Section of Intercity Railway. Issue 5 (May 2023) - Cui, Xiaolu; Li, Jingchen; Bao, Pengyu; Yang, Zongchao; Ren, Zhaohong; Xu, Xiangyang
Focusing on the mechanism of the abnormal phenomenon of rail corrugation on the low rail of small-radius curve section of Guangzhou–Zhuhai intercity railway, the distribution regularities and the track irregularities are studied through the overall and local field surveys. Then, the dynamic model of vehicle-track system on the section is established to explore the wheel-rail dynamic characteristics. Next, the relevant finite element model of the wheel-rail system and the wear model of rail corrugation are established. The friction self-excited vibration analysis and feedback vibration analysis are carried out to investigate the dynamic causes of such abnormal rail corrugation. Field survey proposes that the dominant wavelength of the abnormal rail corrugation is 200–300 mm and the sub-wavelength is 70–100 mm. Analyses show that the friction self-excited vibration of the multi-wheelset-track system caused by the saturated creep force on the guide wheelset in the small-radius section may induce the rail corrugations with these two wavelengths. The possibility of inducing the rail corrugation with 200–300 mm wavelength is greater. On the other hand, the feedback vibration of corrugated wear will aggravate the development of the two corrugated wears. Overall, the generation and development of the abnormal rail corrugations are affected by the self-excited vibration of the wheel-rail system and the feedback vibration of track irregularity.